Viral Phenomena and Social Capital in the Case of the Abandoned Luxury House of Tiko and Mrs. Eny - Yuni Retnowati (Indonesian Journal of Advanced Research, 2023)
The story of Tiko caring for his mother, who has mental disorders, in an abandoned luxury house in the East Jakarta area has become viral because of Bang Brew TV's YouTube content uploads. The virality of social media content can form social capital. Among YouTubers, social capital drives collective action in the form of voluntary work cleaning Tiko's house. Meanwhile, the community was encouraged to provide food assistance, household furniture, cooking utensils, and house painting materials. The purpose of writing is to explain : (1) the viral process of social media content, (2) the role of social media in forming social capital, and (3) social capital in driving collective action.The research used is library research. The study results show that the virality of social media content arises due to the habit of sharing information that unwittingly consumes and produces information simultaneously. Social media acts as a means of dissemination of information and self-presentation that can form relationships, and this is where social capital is formed, which in turn encourages individuals and groups to work together to carry out certain activities.